Pengaruh Public Service Motivation Dan Organizational Citizenship Behavior Terhadap Kinerja Organisasi Pemerintahan - Puput Tri Tri Komalasari; Moh. Nasih; Teguh Prasetio (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2009)
Public sector organizations, namely governments, are described as “non-productive and inefficient organization”. This negative image of public sector organizations has arisen as a consequence of low public sector organization performance. Public sector performance improvement can be done by manipulating motivational dimensions of public service employee. This research aims to empirically test effect of public service motivation and organizational citizenship behavior (OCB) on organizational performance in the public sector of Indonesia. In addition, this study also focuses on individual factor of motivation, such as job satisfaction and organizational commitment. This paper employed 108 respondents that were sampled using convenient sampling. The result showed that there were positive significant influences of public service motivation and job satisfaction on organizational performance. Unfortunately, this study failed to give a proof that OCB influences organizational performance. Moreover, this study showed that there is differences level of motivational between men and women. On average, women have job satisfaction and public service motivation higher than men. This implies that women more satisfy at work than men, and women more likely to value intrinsic reward than men